PREVALENCE OF NON-THROMBOEMBOLIC INCIDENTAL FINDINGS ON COMPUTED TOMOGRAPHY-PULMONARY ANGIOGRAPHY FOR PULMONARY - Bozorgmehr, Rama; Pishgahi, Mehdi; Mohaghegh, Pegah; Bayat, Marziye; Khodadadi, Parastou; Ghafori, Ahmadreza (International Journal of Cardiovascular Practice)
Introduction: Computed Tomography-Pulmonary Angiography (CTPA) is a noninvasive imaging modality for direct diagnosis of pulmonary thromboembolism. The potential advantage of CTPA is possible alternative and incidental findings in cases that PTE is ruled out. This study was performed to determine the prevalence of incidental findings in CTPA in patients suspected to have PTE.Methods: This cross-sectional retrospective study was performed in patients with suspected PTE admitted to Shohada-e-Tajrish Hospital in 2014 and 2015 and underwent CTPA for final diagnosis. Incidental findings in CTPA and associated clinical symptoms were assessed.Results: According to CTPA performed in 188 patients, PTE was diagnosed in 61 cases (32.4%). Prevalence of incidental abnormal findings in the two groups with and without PTE were 93.7% and 90.9%, respectively. The most common incidental finding was pleural effusion (42%). There was no significant association between clinical symptoms and incidental findings in CTPA in patients with suspected pulmonary embolism (P > 0.05). The only significant finding was association between lung mass and tachypnea (P=0.007).Conclusion: In patients with primary clinical symptoms of suspected pulmonary embolism, in most cases there was a wide range of incidental findings and simultaneous pathologies in CTPA mimicking the primary symptoms of pulmonary embolism. However, in this study there was no significant association between clinical symptoms and incidental findings. Determination of definite indications of CTPA in patients with suspected pulmonary embolism is necessary.